2017
DOI: 10.1088/1742-6596/853/1/012011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of acute lymphocyte leukemia using k-nearest neighbor algorithm based on shape and histogram features

Abstract: Abstract. Leukemia is a type of cancer which is caused by malignant neoplasms in leukocyte cells. Leukemia disease which can cause death quickly enough for the sufferer is a type of acute lymphocyte leukemia (ALL). In this study, we propose automatic detection of lymphocyte leukemia through classification of lymphocyte cell images obtained from peripheral blood smear single cell. There are two main objectives in this study. The first is to extract featuring cells. The second objective is to classify the lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…In their empirical study, they determined that k = 4 performed the best classiication. Purwanti et al [184] tried all the odd values of k from 1 to 15 and concluded that k = 7 gives the optimal results for the given dataset. Bhattacharjee et al [93] used the value of k as 1 to perform the classiication using low computational resources.…”
Section: Classificationmentioning
confidence: 99%
“…In their empirical study, they determined that k = 4 performed the best classiication. Purwanti et al [184] tried all the odd values of k from 1 to 15 and concluded that k = 7 gives the optimal results for the given dataset. Bhattacharjee et al [93] used the value of k as 1 to perform the classiication using low computational resources.…”
Section: Classificationmentioning
confidence: 99%
“…6. Many conventional supervised learning methods have been used to classify leucocytes in microscopic blood smear images, such as Support Vector Machine (SVM) [32][33][34], Naive Bayes (NB) [35][36][37], K-Nearest Neighbor (KNN) [38][39][40], and Artificial Neural Network (ANN) [41][42][43]. Some popular WBCs nuclei detection techniques are identified and reviewed, which are presented in Table 2.…”
Section: A Tml and DL For Leucocytes Classification In Blood Smear Imentioning
confidence: 99%
“…Purwanti et. al., [21] propose an automated method for detecting lymphocyte leukemia by classifying single lymphocyte images obtained from peripheral blood smears. This study has two primary objectives.…”
Section: Related Workmentioning
confidence: 99%